The IMPLEMENTASI SISTEM BOOST CONVERTER DAN PENGUKURAN PADA ALAT PENGUSIR HAMA BERBASIS ARDUINO DAN LABVIEW - Iman, Muhammad Rifci Imanullah (Universitas Islam Balitar Blitar, 2023)
In this study, the authors looked at the problem of pest repellent devices that produce ultrasonic wave sounds above 20Khz that can only be heard by bats, whales, and rats. batteries that are charged by solar panels. However, the battery voltage will decrease as the use of power from the battery decreases due to usage. In this research, a boost converter circuit was chosen to increase the battery so that it stabilizes at 13V. The boost converter control uses Arduino with Pulse Width Modulation (PWM) output to trigger MOSFET. The results of measuring the value and graph of voltage and current data will be displayed on LabView software in order to facilitate data reading.